Stopping Tuberculosis at the Gate: The Role of M. tuberculosis Adhesins in Infection and Intervention - Haoyan Yang; Yinuo Ma; Xinkui Lei; Siyu Chai; Sigen Zhang; Guimin Su; Songping Li; Lin Du (Vaccines)
The global burden of tuberculosis (TB), exacerbated by the rise of drug-resistant Mycobacterium tuberculosis (M. tuberculosis), underscores the need for alternative intervention strategies. One promising approach is to block the infection at its earliest stage—bacterial adhesion to host cells—thereby preventing colonization and transmission without exerting selective pressure. Adhesins, surface-exposed molecules mediating this critical interaction, have therefore emerged as attractive targets for early prevention. This review outlines the infection process driven by bacterial adhesion and describes the architecture of the M. tuberculosis outer envelope, emphasizing components that contribute to host interaction. We comprehensively summarize both non-protein and protein adhesins, detailing their host receptors, biological roles, and experimental evidence. Recent progress in the computational prediction of adhesins, particularly neural network-based tools like SPAAN, is also discussed, highlighting its potential to accelerate adhesin discovery. Additionally, we present a detailed, generalized workflow for predicting M. tuberculosis adhesins, which synthesizes current approaches and provides a comprehensive framework for future studies. Targeting bacterial adhesion presents a therapeutic strategy that interferes with the early stages of infection while minimizing the risk of developing drug resistance. Consequently, anti-adhesion strategies may serve as valuable complements to conventional therapies and support the development of next-generation TB vaccines and treatments.